Development of a quality assurance review framework for health impact assessments. Issue 2 (4th March 2019) - Green, Liz; Gray, Benjamin J.; Edmonds, Nerys; Parry-Williams, Lee
ABSTRACT: The use of health impact assessments (HIAs) has rapidly increased over the last two decades and has been undertaken to evaluate the health implications of many new projects across the globe. In July 2017, Wales became the first country to legislate for broad approach HIAs, i.e. it considers not only environmental health effects but the social determinants of health, well-being and inequalities. Although the introduction of statutory HIA will ensure the use of HIAs, experts have expressed concerns that legislative measures could lead to poor-quality HIAs and associated reports. This paper outlines the development process and analytical reflections of a quality assurance (QA) review framework for HIAs. The framework has been developed over a 2-year period which allowed the collective intellectual capital behind it to evolve in response to practice-based learning. A standardised form of QA for all types and levels of HIA will provide greater clarity regarding the required criteria for conducting and completing an HIA and ensuring this takes place in a robust, interdisciplinary and inter-sectoral manner. Therefore, this QA review framework should fit into existing HIA practice and complement other tools such as best practice guidance to sustain the global reputation of HIA.